EFFECT OF TEMPERATURE ON INHIBITION EFFICIENCY OF EUGENOL FOR COPPER CORROSION - Samontha, Atitaya; Jitsamak, Natthawut (Life Sciences and Environment Journal, 2019)
The effect of temperature on inhibition efficiency of eugenol for copper (Cu) corrosion was studied using the weight loss measurement, and scanning electron microscope (SEM). The corrosion of Cu has attracted much attention because Cu has been applied as raw material in various industries. Nowadays the popular method to prevent/reduce Cu corrosion is the addition of green corrosion inhibitor. In this work, eugenol, a natural fragrance and flavor extracted from plants, was applied as an eco-friendly corrosion inhibitor. Eugenol could be used to reduce the corrosion of Cu in the presence of 1 M HCl. However the inhibition efficiency of eugenol for Cu plates at 1 M HCl was found to decrease with increasing temperature from 30°C to 70°C. The data from the weight loss measurement corresponded with images from SEM. Eugenol was found to perform well as a corrosion inhibitor of Cu and also possibly provided another capability of Thai tradition herbs in this research.